Swiprosin-1/EFhd2 Controls B Cell Receptor Signaling through the Assembly of the B Cell Receptor, Syk, and Phospholipase C gamma 2 in Membrane Rafts - Kroczek, Carmen; Lang, Christiane; Brachs, Sebastian; Grohmann, Marcus; Duetting, Sebastian; Schweizer, Astrid; Nitschke, Lars; Feller, Stephan M.; Jäck, Hans-Martin; Mielenz, Dirk (Journal of Immunology, 2010)
Compartmentalization of the BCR in membrane rafts is important for its signaling capacity. Swiprosin-1/EFhd2 (Swip-1) is an EF-hand and coiled-coil-containing adaptor protein with predicted Src homology 3 (SH3) binding sites that we identified in membrane rafts. We showed previously that Swip-1 amplifies BCR-induced apoptosis; however, the mechanism of this amplification was unknown. To address this question, we overexpressed Swip-1 and found that Swip-1 amplified the BCR-induced calcium flux in WEH1231, B62.1, and Bal17 cells. Conversely, the BCR-elicited calcium flux was strongly attenuated in Swip-1-silenced WEH1231 cells, and this was due to a decreased calcium mobilization from intracellular stores. Complementation of Swip-1 expression in Swip-1-silenced WEH1231 cells restored the BCR-induced calcium flux and enhanced spleen tyrosine kinase (Syk) tyrosine phosphorylation and activity as well as SLP65/BLNK/BASH and phospholipase C gamma 2 (PLC gamma 2) tyrosine phosphorylation. Furthermore, Swip-1 induced the constitutive association of the BCR itself, Syk, and PLC gamma 2 with membrane rafts. Concomitantly, Swip-1 stabilized the association of BCR with tyrosine-phosphorylated proteins, specifically Syk and PLC gamma 2, and enhanced the constitutive interaction of Syk and PLC gamma 2 with Lyn. Interestingly, Swip-1 bound to the rSH3 domains of the Src kinases Lyn and Fgr, as well as to that of PLC gamma. Deletion of the predicted SH3-binding region in Swip-1 diminished its association and that of Syk and PLC gamma 2 with membrane rafts, reduced its interaction with the SH3 domain of PLC gamma, and diminished the BCR-induced calcium flux. Hence, Swip-1 provides a membrane scaffold that is required for the Syk-, SLP-65-, and PLC gamma 2-dependent BCR-induced calcium flux. The Journal of Immunology, 2010, 184: 3665-3676.